Diabetic Gastroenteropathy: A Complication of Diabetes Mellitus - Alvin Hartanto Kurniawan; Benedictus Hanjaya Suwandi; Ulfa Kholili (Acta Medica Indonesiana)
Diabetic gastroenteropathy is a common complication in prolonged diabetic patients, particularly patients with poor glycemic control or other complications, including all form of diabetic complication on the gastrointestinal tract, which prompts various symptoms of heartburn, abdominal pain, nausea, vomiting, even constipation, diarrhea, and fecal incontinence. The underlying pathophysiology of this complication manifestations are different on each organ or symptom, but may include autonomic nervous system neuropathy, loss of Interstitial Cell of Cajal as gastric muscle pacemaker leading to dysmotility, impair of liquid transportation and motoric function, as well as hyperglycemia causing oxidative stress, and other factors like Insulin-Growth Factor I inducing smooth muscle atrophy. Diabetic gastroenteropathy is one of major morbidity on diabetes mellitus patients. Patients with this complication need to be well diagnosed and ruled out other diagnosis possibilities. Management of the complication includes resolving main symptoms and maintaining good glycemic control. With growing number of diabetes mellitus patients and the prevalence of diabetic gastroenteropathy complication not being well recorded, caused by lack of attention and knowledge of healthcare provider in identifying the complication; it is important to be able to identify and to give early treatment to diabetic gastroenteropathy patients, to increase quality of life and maintain glycemic control of the patient.